If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 4) = 3x + 14 Reorder the terms: 5(4 + x) = 3x + 14 (4 * 5 + x * 5) = 3x + 14 (20 + 5x) = 3x + 14 Reorder the terms: 20 + 5x = 14 + 3x Solving 20 + 5x = 14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 20 + 5x + -3x = 14 + 3x + -3x Combine like terms: 5x + -3x = 2x 20 + 2x = 14 + 3x + -3x Combine like terms: 3x + -3x = 0 20 + 2x = 14 + 0 20 + 2x = 14 Add '-20' to each side of the equation. 20 + -20 + 2x = 14 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 14 + -20 2x = 14 + -20 Combine like terms: 14 + -20 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 625=(x^2)+(x^2)+6x+9 | | 9k-32=6k+8 | | x/7=5 | | 12x+7y=-35 | | x^3+125y^3= | | k+3(3)=45 | | 500-3x=275 | | 6(-1-d)=-42 | | n-10=.3n-7-.3n | | (3u+7)(6-u)=0 | | 2-11-19= | | b^4-32b^2+256= | | 70uv-91uw= | | 2x-19= | | 1/3(6z+10)= | | 7b^2+43b+40=0 | | 7(n+3)=6(n-3) | | 13t+8=4t+73 | | 2(0d-4)=2d+8 | | 5t-14=14 | | 27g+9=5g+31 | | -3(-5z+12)=-2z-36 | | 7b^2+34b+40=0 | | 16x^3+24x^2+9x+1=0 | | 2b+5=-9 | | 10+3(3x+6)= | | 9m+14=2 | | 11=8x+5-5x | | 10p-15=5p+30 | | 3*3+12=3 | | X-3=-24 | | 12x-5=6(2x-3) |